2017
DOI: 10.1007/s00006-017-0801-3
|View full text |Cite
|
Sign up to set email alerts
|

3-ary Hom-Lie Superalgebras Induced By Hom-Lie Superalgebras

Abstract: The purpose of this paper is to study the relationships between a Hom-Lie superalgebra and its induced 3-ary-Hom-Lie superalgebra. We provide an overview of the theory and explore the structure properties such as ideals, center, derived series, solvability, nilpotency, central extensions, and the cohomology.1 of how to construct ternary multiplications from the binary multiplication of a Hom-Lie algebra, a linear twisting map, and a trace function satisfying certain compatibility conditions; and it was shown t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…In [47], the authors introduced a construction of a 3-Hom-Lie superalgebra from a Hom-Lie superalgebra. It is called 3-Hom-Lie superalgebra induced by Hom-Lie superalgebra.…”
Section: N-hom-lie Superalgebras Induced By Hom-lie Superalgebrasmentioning
confidence: 99%
See 1 more Smart Citation
“…In [47], the authors introduced a construction of a 3-Hom-Lie superalgebra from a Hom-Lie superalgebra. It is called 3-Hom-Lie superalgebra induced by Hom-Lie superalgebra.…”
Section: N-hom-lie Superalgebras Induced By Hom-lie Superalgebrasmentioning
confidence: 99%
“…, y n ) = 0. In the following, we generalise the notion of supertrace introduced in [47] for the even multilinear form. Proof.…”
Section: N-hom-lie Superalgebras Induced By Hom-lie Superalgebrasmentioning
confidence: 99%
“…These quasideformations lead to quasi-Lie algebras, a generalized Lie algebra structure in which the skew symmetry and Jacobi conditions are twisted. Hom-Lie algebras, Hom-Lie superalgebras, Hom-Lie bialgebras, Hom-Lie 2-algebras, and quasi-Hom-Lie algebras are discussed in [4][5][6][7][8][9][10][11][12][13][14]. The n-ary Hom-Nambu-Lie algebras have been introduced in [15].…”
Section: Introductionmentioning
confidence: 99%
“…Particularly it was proved that Lie superalgebra gl(m, n) of (m, n)-block matrices induces the 3-Lie superalgebra if we endow it with a graded triple bracket, constructed with the help of binary graded commutator of gl(m, n) and the supertrace of (m, n)-block matrix. In [9] this approach was extended to 3-ary Hom-Lie superalgebras and the authors showed that given a Hom-Lie superalgebra and its representation one can construct the 3-ary Hom-Lie superalgebra, whose graded triple Lie bracket is constructed by means of binary graded Lie bracket of Hom-Lie superalgebra and the supertrace. The authors of [9] explored the structures of induced 3-ary Hom-Lie superalgebras such that ideals, center, derived series and central extensions.…”
Section: Introductionmentioning
confidence: 99%